Preparation and Characterization of Chitosan/Agar Blended Films: Part 2. Thermal, Mechanical, and Surface Properties - Esam A. Elhefian; Mohamed Mahmoud Nasef; Abdul Hamid Yahaya (E-Journal of Chemistry)
Chitosan/agar (CS/AG) films were prepared by blending different proportions of chitosan and agar (considering chitosan as the major component) in solution forms. The thermal stability of the blended films was studied using thermal gravimetric analysis (TGA). It was revealed that chitosan and agar form a compatible blend. Studying the mechanical properties of the films showed a decrease in the tensile strength and elongation at break with increasing agar content. Blending of agar with chitosan at all proportions was found to form hydrogel films with enhanced swelling compared to the pure chitosan one. Static water contact angle measurements confirmed the increasing affinity of the blended films towards water suggesting that blending of agar with chitosan improves the wettability of the obtained films.